The susceptibility of ventricular arrhythmia to aconitine in conscious Lyon hypertensive rats - Li Min; Wang Jin; Xie He-hui; Shen Fu-ming; Su Ding-feng (Acta Pharmacologica Sinica, 2016)
Aim: The present work was designed to investigate the relationship between hemodynamic parameters and the susceptibility of ventricular arrhythmia to aconitine in conscious Lyon hypertensive rats (LH). Methods: Male LH and Lyon low blood pressure rats (LL) were used. After the determination of baroreflex sensitivity (BRS), ventricular arrhythmia was induced by aconitine infusion in conscious rats. Blood pressure (BP) was recorded during the period of infusion. Results: Compared with the LL rats, the LH rats possessed significantly higher BP, blood pressure variability and lower BRS. The threshold of aconitine required for ventricular fibrillation and cardiac arrest in the LH rats were significantly lower than those in the LL rats. It was found that all the hemodynamic parameters studied were not correlated with the threshold of aconitine required for arrhythmia, with the exception of BRS, which was positively related to the threshold of aconitine required for ventricular premature beat. Conclusion: The LH rats possessed greater susceptibility to aconitine-induced ventricular arrhythmias when compared to the LL rats. This greater susceptibility could not be attributed to any one of the hemodynamic parameters alone studied in the LH rats. It is proposed that various hypertension-associated abnormalities, including the abnormal hemodynamics, may co-contribute to this vulnerability to ventricular arrhythmias.